2021
DOI: 10.3390/met11020229
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Composite Deck Slab Made of Cold-Formed Profiled Steel Sheeting

Abstract: An experimental investigation is performed on various cold-formed profiled sheets to study the connection behavior of composite deck slab actions using bolted shear connectors. Various profiles like dovetailed (or) re-entrant profiles, rectangular profiles and trapezoidal profiles are used in the present investigation. This experimental investigation deals with the evaluation of various parameters such as the ultimate load carrying capacity versus deflection, load versus slip, ductility ratio, strain energy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…According to Rackham et al [2], the bearing capacity of composite slabs is normally dictated by the shear strength rather than by yielding of profiled steel deck. In most cases, the indentations and embossments of the profiled steel deck were found to be effective in magnifying the shear strength and increase the ultimate load [58], [59]. In this experimental study, higher bearing capacity was achieved through higher bending stiffness.…”
Section: Failure Modementioning
confidence: 61%
“…According to Rackham et al [2], the bearing capacity of composite slabs is normally dictated by the shear strength rather than by yielding of profiled steel deck. In most cases, the indentations and embossments of the profiled steel deck were found to be effective in magnifying the shear strength and increase the ultimate load [58], [59]. In this experimental study, higher bearing capacity was achieved through higher bending stiffness.…”
Section: Failure Modementioning
confidence: 61%
“…This requires the formation of a multi-criteria structure of quality indicators, reflecting a number of required operational properties of the vehicle. The use of high-quality engineering materials also has a significant impact on the operation process, examples of which are given in [21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental studies on composite deck panels with shear connectors can be found in the literature [1][2][3][4][5][6][7][8][9][10]. However, limited experimental tests have been performed on composite deck panel without shear connectors.…”
Section: Literature Reviewmentioning
confidence: 99%